PENGELOLAAN KEUANGAN NELAYAN KERANG HIJAU DI DESA KETAPANG, KECAMATAN MAUK KABUPATEN TANGERANG, PROVINSI BANTEN - Rahmani, Urip; Patanda, Mercy; Ernaningsih, Dwi; Telussa, Riena F; Limbong, Mario; Stefhany, Yosi (Community Services and Social Work Bulletin, 2022)
Tangerang's green mussel farms are expanding. Green mussels grow swiftly and easily, thus many people plant them. Boatmen, divers, bamboo and rope sellers, clam shell peelers, clam boilers, stroller-selling clam sellers, and rice stalls that serve green clam delicacies all work hard on green mussel farms. Green mussel growers and other coastal towns rely heavily on sales. To make a life, farmers need excellent financial arrangements because yields can vary. This prompted financial management coaching for green mussel fisherman in Ketapang Village, Mauk District, Tangerang Regency. The activity took place from April to August 2022. Green mussel farmers should be able to run their enterprises and manage their money to enhance them. Counseling participants are mostly employed, according to their earnings. Most counseling clients don't know much about food-industry green mussels. Counseling changed everything. The counseling findings demonstrate participants' financial literacy. Managing revenue and expenses, borrowing tactics from financial institutions, or learning about business growth budgets.